Enforcement Gaps in Child Protection Law: Managing Strategy of Violence on Students in Islamic Boarding Schools and the Limits of Legal Compliance in Indonesia - Kisbiyanto Kisbiyanto (UIN Sunan Gunung Djati, 2025)
This study investigates enforcement gaps in Indonesia’s child protection law by focusing on violence in Islamic boarding schools (pesantren) in Kudus. The research aims to examine why violence against children persists despite the existence of comprehensive statutes such as Law No. 35 of 2014 on Child Protection, Law No. 20 of 2003 on the National Education System, Law No. 18 of 2019 on Pesantren, and Law No. 12 of 2022 on Sexual Violence Crimes. Using a qualitative socio-legal method, the study combines normative legal analysis with empirical case studies drawn from media reports, NGO documentation, and secondary academic sources. The findings reveal four major enforcement gaps: limited accessibility of reporting mechanisms due to fear and hierarchical power relations; cultural normalization of violence through ta’zir as disciplinary education; fragmented institutional coordination without intersectoral SOPs; and the frequent use of restorative justice settlements that disadvantage victims. These results underscore that legal reforms alone are insufficient without accompanying cultural transformation, integrated institutional mechanisms, and community-based engagement. The study contributes to child protection discourse by proposing an integrative approach that harmonizes statutory law with religious moderation and communal values, while aligning with international standards such as the Convention on the Rights of the Child (CRC). The originality of this research lies in its contextual focus on pesantren, a relatively underexplored site in child protection scholarship, thereby enriching international debates on law, culture, and the protection of children in religious education settings.